2021
DOI: 10.46717/igj.54.2a.8ms-2021-07-29
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Evaluation of Groundwater in Al-Khasfa Area within Haditha, Western Iraq

Abstract: The main aim of the research is to study the groundwater quality in Al-Khasfa area within Haditha district, western Iraq. To assess the groundwater, eighteen groundwater samples in the study area were collected and analyzed for major cations and anions. Results indicated that groundwater samples in the study area are between neutral and light alkaline, slightly brackish, and highly mineralized. The hydrochemical formula of the groundwater samples indicates the Ca-SO4 type dominance, except wells number 16 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Drinking water is becoming contaminated with cadmium as a result of paint and battery waste, eroding natural deposits, emptying from metal refineries, and corroding galvanized pipes.The concentration values of Cadmium for specific regions during the research seasons are displayed in Table (4). Cadmium concentrations as of measured in ppm for samples during the study seasons, the results showed a range.…”
Section: Average Physical and Chemical Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Drinking water is becoming contaminated with cadmium as a result of paint and battery waste, eroding natural deposits, emptying from metal refineries, and corroding galvanized pipes.The concentration values of Cadmium for specific regions during the research seasons are displayed in Table (4). Cadmium concentrations as of measured in ppm for samples during the study seasons, the results showed a range.…”
Section: Average Physical and Chemical Propertiesmentioning
confidence: 95%
“…Heavy metal pollution is problem that has received widespread attention the world [3]. The quality of groundwater is not only affected by natural factors such as the rocks of the aquifer, the nature of the interaction between groundwater and aquifer materials, and the nature of recharge water [4]. But they can also be altered by human activities either by affecting the hydrological cycle or by polluting groundwater systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…The climate has considered an important factor affecting the water balance and its difference from one season or year to another, and from place to place, depending on latitude, distance to the sea, vegetation, presence or absence of mountains, or other geographical factors, where rainfall and evaporation are the basic factors in the hydrological cycle. Studying climate change in a region is important because it is closely related to quantities and water quality [4]. The study area is undergoing the influences of the dry desert climate and, to a lesser degree, the influences of the climate of the Mediterranean and the Arabian Gulf [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several geological, hydrological, hydrogeological, hydrochemical, and geochemical studies has been done in this area [2,3.4.5]. Some studies used other methods to calculate the water budget, including: [6] analyzing the climatic parameters, [7] Lerner's methods, and [8] used the SWAT model to know the hydrological condition.…”
Section: Introductionmentioning
confidence: 99%